Transfusion Ethics in a Pediatric Jehovah's Witness Trauma Patient: Simulation Case - Mathew Malkin; John Lenart; Catherine A. Walsh; Michelle Woodfin; Marissa Vadi (Association of American Medical Colleges, 2016)
Abstract Introduction Current ethical practice allows for adult patients with decision-making capacity to refuse blood transfusion, even at the cost of high morbidity or mortality. However, for an adult patient who is of the Jehovah's Witness faith, an unwanted blood transfusion confers a psychospiritual cost to the patient and a financial cost to health care entities. The ethical boundaries are increasingly ambiguous with minors who are members of the Jehovah's Witness faith. This simulation experience intends to identify and address knowledge gaps in the care of minors in an emergent setting using a biomedical ethics framework. Methods This scenario provides an immersive simulation experience involving a 12-year-old Jehovah's Witness patient requiring emergent laparotomy for splenic hemorrhage. Patient interview (via simulation manikin with instructor voice) and care handoff take place in an operating room setting. The learner ascertains the patient's and family's refusal of blood products. Induction of general anesthesia results in profound patient hypotension secondary to acute blood-loss anemia. Pulseless electrical activity results if packed red blood cells are not administered. Ethical principles require the learner to impose an unwanted lifesaving therapy on a minor patient over the objections of family members. Secondly, the anesthesia provider must advocate for transfusion on these ethical grounds against a well-meaning but ultimately misguided surgeon who opposes transfusion. An included learner evaluation form based on ACGME core competencies facilitates postsimulation debriefing. Results Participants were primarily anesthesia residents and fellows. Anecdotally, the residents said that it "felt good to be an attending" and that the simulation helped them appreciate how important conflict resolution skills are in the OR setting. Additionally, faculty appreciated the ability to assess the development of crucial assertiveness skills, with the option of remediating incorrect behavior during the debriefing. Discussion This simulation experience provides experience in the emergent medical management of a pediatric trauma patient while also incorporating specific ethical consent issues unique to pediatric and trauma patient populations. Furthermore, this experience develops professionalism skills and practice in assertive patient advocacy.